ANALISIS WACANA ”KEPANTASAN BERSIKAP” DALAM STAND UP COMEDY PANDJI PRAGIWAKSONO - Altin Muntiara Sari; Rakhmad Saiful Ramadhani; Fatihatul Lailiyah (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2021)
Nowadays everyone is free to have an opinion, the existence of social media adds to the potential for freedom of opinion. No wonder there are more and more cases of offense, this is due to the appropriateness of attitude. Appropriate behavior is an attempt to minimize actions/speech that have the potential to offend individuals/groups. One of the impacts of the appropriateness of attitude is the change in the term crazy to people with mental disorders (ODGJ), disability is refined into disability. Appropriate behavior can be applied in Indonesia considering the friendly Indonesian people, but this sometimes clashes with comedy because sometimes comedians make comedy by ignoring the appropriateness of behavior. One of them was Pandji Pragiwaksono who violated the appropriateness of attitude. In the video Stand Up Comedy